2022
DOI: 10.1371/journal.pbio.3001786
|View full text |Cite
|
Sign up to set email alerts
|

A caspase–RhoGEF axis contributes to the cell size threshold for apoptotic death in developing Caenorhabditis elegans

Abstract: A cell’s size affects the likelihood that it will die. But how is cell size controlled in this context and how does cell size impact commitment to the cell death fate? We present evidence that the caspase CED-3 interacts with the RhoGEF ECT-2 in Caenorhabditis elegans neuroblasts that generate “unwanted” cells. We propose that this interaction promotes polar actomyosin contractility, which leads to unequal neuroblast division and the generation of a daughter cell that is below the critical “lethal” size thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
(127 reference statements)
1
1
0
Order By: Relevance
“…In our dataset, an amount of 93 sister cell pairs with one non-apoptotic cell and one apoptotic cell are recorded without data point loss at both their first appearances in at least one C. elegans wild-type embryo sample. It’s found that the majority of apoptotic cells (78 out of 93 sister cell pairs, >80%) acquire both smaller average volume and surface area than those of their sister cells right after the cytokinesis of their mother cells, reproducibly among embryo samples and regardless of lineal origin (Figure 6C; Figure 6D; Figure S18; Table S12); these quantitative results mean that the initial cell size asymmetry between an apoptotic cell and its sister cell, previously reported in specific population like neuroblast, is actually at work in a global manner throughout C. elegans embryogenesis [Cordes et al, Development , 2006; Sethi et al, PLoS Biol. , 2022].…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…In our dataset, an amount of 93 sister cell pairs with one non-apoptotic cell and one apoptotic cell are recorded without data point loss at both their first appearances in at least one C. elegans wild-type embryo sample. It’s found that the majority of apoptotic cells (78 out of 93 sister cell pairs, >80%) acquire both smaller average volume and surface area than those of their sister cells right after the cytokinesis of their mother cells, reproducibly among embryo samples and regardless of lineal origin (Figure 6C; Figure 6D; Figure S18; Table S12); these quantitative results mean that the initial cell size asymmetry between an apoptotic cell and its sister cell, previously reported in specific population like neuroblast, is actually at work in a global manner throughout C. elegans embryogenesis [Cordes et al, Development , 2006; Sethi et al, PLoS Biol. , 2022].…”
Section: Introductionsupporting
confidence: 58%
“…, 2018]. Another previously studied relationship is the small cell size and apoptotic cell fate [Cordes et al, Development , 2006; Sethi et al, PLoS Biol. , 2022]; taking two C. elegans embryonic apoptotic cells, MSpaapp and ABprpppppa, as examples, the former proceeds apoptosis as soon as it’s produced while the latter is first involved in the development of spike tail and then proceeds apoptosis at very late stage [Sulston et al, Dev.…”
Section: Introductionmentioning
confidence: 99%